2022
DOI: 10.1002/vms3.705
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response to P4‐PGF‐FSH treatment in Suffolk sheep and P4‐PGF‐PMSG synchronization in cross‐bred ewes, for IVD and ET protocol

Abstract: Background:The success of an embryo transfer protocol in sheep depends on many factors, but the choice of drugs for the desired superovulation as well as the conception rate (CR) are most essential. Reproductive activity in sheep is characterized by a seasonality influenced by several factors such as photoperiod, latitude, temperature, nutrition and breed. Reproductive seasonality and nutritional condition are the main factors that influence embryo production in sheep. In sheep, some anatomical peculiarities l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…In the present study, CL count was higher compared to other studies in sheep that found an average of 7 (Lagares et al, 2021) to 9 (Ciornei et al, 2022) CL / ewe using the same commercial formulation of pFSH and doses between 250 to 500 IU.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In the present study, CL count was higher compared to other studies in sheep that found an average of 7 (Lagares et al, 2021) to 9 (Ciornei et al, 2022) CL / ewe using the same commercial formulation of pFSH and doses between 250 to 500 IU.…”
Section: Discussioncontrasting
confidence: 83%
“…response in approximately 90% of animals, as observed in studies of D' Alessandro et al (1996) and Cordeiro et al (2003). This study found a similar or even higher mean CL count (10.1-13.5/ewe) with reduced doses of pFSH (250-400 IU), in comparison to other studies using 500 or 750 IU (8.3-9.1/ewe) Ciornei et al, 2022). Furthermore, it confirms that a better SOV response is directly related to a greater number of recovered structures.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, several researchers such as Donaldson et al (1986), Nowshari et al (1995), Boscos et al (2002), found that a low‐LH:FSH preparation may be better for follicle development and obtaining more embryos transferring. On contrary, other researchers showed that a responding donor can produce an average of 8–12 embryos (limit from 1 to 30) depending on the breed, time of year and condition of the animal embryos (Ciornei et al, 2022; Ghosh et al, 2017; Menchaca et al, 2009). In our study, the number of corpora lutea per donor averaged 12.3 ± 0.87 for both treatment regimens, which is also at the upper limit of performance.…”
Section: Discussionmentioning
confidence: 98%
“…The main factor of donors' response to superovulation is gonadotropin, which directly affects embryos recovery number from one donor (Pérez-Sandoval et al, 2019). Anterior pituitary gland produces FSH preparations and also it contains other biologically active substances such as LH, the amount of FSH and LH and their activity may vary depending on animal breed and different preparations (Braileanu et al, 1998;Ciornei et al, 2022;Donaldson et al, 1986;Luna-Palomera et al, 2019). In our present study, two follicle-stimulating preparations (Folltropin-V and FSH-P) were used to stimulate superovulation in Charolais and Ile-de-France ewes.…”
Section: Ta B L Ementioning
confidence: 99%
“…Since ET in sheep is a well-known but insufficiently applied reproductive biotechnology. Therefore, there has been a need for an optimization and a continuous improvement of the techniques (Ciornei et al, 2022). Hence, the main objective of this study was to evaluate the conception rate obtained after ET in Mongolian sheep.…”
mentioning
confidence: 99%